Analysis of residual thermal stresses in MoSi2 based laminated composites. (November 2017) - Jain, Manoj Kumar; Das, Jiten; Deb, S.; J, Subrahmanyam; Ray, S.
Abstract: The residual thermal stresses of MoSi2 -SiCp + refractory metal foil laminated composites are estimated, in this paper, by both finite element methods (FEMs) as well as analytical expressions. It is observed in the present study that the refractory metal foils are found to possess compressive stresses, while the MoSi2 -SiCp matrix layer is under tensile stresses. The Nb foil reinforced laminated composite is found to possess the lowest residual stresses owing to a lower thermal expansion mismatch between MoSi2 -SiCp matrix and the Nb foil as compared to the Mo and Ta foils. Highlights: An attempt has been made in this study to evaluate the nature and magnitude of residual thermal stresses in (MoSi2 - SiCp )/refractory metal foils laminated composites by theoretical methods. In case of MoSi2 -SiCp + refractory metal foil laminated composites, the refractory metal foils are found to possess compressive stresses, while the MoSi2 -SiCp matrix layer is under tensile stresses. The Nb foil reinforced laminated composite is found to possess the lowest residual stresses owing to a lower thermal expansion mismatch between MoSi2 -SiCp matrix and the Nb foil as compared to the Mo and Ta foils.